Integrated Nutrient Management Practices for Glori lily (Gloriosa superba L.) - Deivasigamani, S.; Thanunathan, K. (Open Access Journal of Medicinal and Aromatic Plants, 2011)
Field experiments were conducted at the farmers’ field, Devanur village, Ariyalur District, Tamilnadu during 2007-2009 to study the effect of Integrated Nutrient Management (INM) practices on the yield performance of Glory lily (Gloriosa superba L.). The experiment was conducted in split-plot design with three replications. The treatments consisted of different organic manures in main plots (M2- farmyard manure (FYM) at 12.5 t ha-1, M3-enriched farmyard manure (EFYM) at 750 kg ha-1 and M4- pressmud compost at 5t ha-1 along with M1-control) and different levels of inorganic nitrogen in sub-plots (S1-100% N, S2-75% N, S3-50% N and S4-25% N along with S0-control). Among the organic manures, application of EFYM at 750 kg ha-1 recorded the highest yield attributes like number of capsules plant-1, number of seeds capsule-1, test weight (g), seed yield and tuber yield. Among the levels of inorganic nutrients , nitrogen application of 100 % recommended N (120 kg ha-1) recorded the highest yield attributes, seed yield and tuber yield. With regard to interaction effect, integrated use of EFYM at750 kg ha-1 and 75% inorganic nitrogen registered the highest values of yield attributes, seed yield and tuber yield.